SISTEM KENDALI ONLINE BERBASIS IOT UNTUK MANIFOLD TABUNG OKSIGEN DENGAN PEMANTAUAN REAL-TIME DAN INTEGRASI ALARM - Abdul Haris Kuspranoto; Zulkhairi; Rodhiyah Mardhiyyah (MEDIKA TRADA, 2025)
Accurate This research develops an Internet of Things (IoT)-based online control system for oxygen cylinder manifolds in medical facilities. This system utilizes pressure sensors, ESP32 modules, and cloud platforms to monitor oxygen pressure in real-time. For example, the pressure sensor used can accurately measure the oxygen pressure in the cylinder and transfer the data to the ESP32 module for processing. Then, the data is sent via Wi-Fi network to a web dashboard and mobile application. For example, medical personnel can easily monitor oxygen pressure from their smartphones, even when they are not in the same room as the oxygen cylinder. In addition, this system is equipped with an automatic alarm mechanism via the Notification App if an anomaly occurs such as a decrease in pressure or leakage. For example, if the oxygen pressure in the cylinder drops below a safe limit, the Notification App will automatically alert medical personnel to take immediate action. The test results showed a response time of less than 4 seconds and a sensor accuracy rate of ±2%. With fast response time and high accuracy, the system can provide timely and accurate information to medical personnel. The system offers an economical and scalable solution to improve the efficiency and safety of oxygen gas distribution in hospitals. In addition, the implementation of this system can reduce operational costs in manual monitoring of oxygen cylinders, saving time and resources. By adopting IoT technology in oxygen management in medical facilities, hospitals can improve the quality of patient care and ensure sufficient oxygen availability consistently.